“INTRA-RACIAL DYNAMICS OF BLACK FACULTY AND BLACK STUDENTS: BARRIERS TO SUCCESS IN THE ACADEMY IN PREDOMINANTLY WHITE INSTITUTIONS” - D. Toliver, Susan; Moore, Penelope J.; Redcross, Natalie (European Scientific Journal, ESJ, 2015)
Intra-racial Black faculty and Black students’ communication at predominantly White institutions poses an additional challenge and source of stress for Black faculty. The view of their role vis-à-vis Black students is at odds with students’ perceptions of Black faculty identity and the Black faculty role impeding Black faculty’s effectiveness as mentors. Black faculty need to address this disconnect in order to increase the academic success of Black students, to decrease Black faculty’s sense of isolation, and to support the interests of their institutions in their attempts to increase Black student retention and multicultural transformation of the academy.